Characterization of Bacillus subtilis and B. licheniformis potentials as probiotic bacteria in Vanamei shrimp feed (Litopenaeus vannamei Boone, 1931) - YULI ANDRIANI; RATU SAFITRI; EMMA ROCHIMA; SARAH DEWI FAKHRUDIN (Nusantara Bioscience, 2017)
Andriani Y, Safitri R, Rochima E, Fakhrudin SD. 2017. Characterization of Bacillus subtilis and B. licheniformis potentials as probiotic bacteria in Vanamei shrimp feed (Litopenaeus Vannamei Boone, 1931). Nusantara Bioscience 9: 188-193. This study aimed to characterize the Bacillus subtilis and Bacillus licheniformis potentials as probiotic bacteria in Vanamei shrimp feed (Litopenaeus vannamei Boone, 1931). A two-phase experimental descriptive method in a laboratory scale was applied in this study. The first phase was the bacterial growth curve observation of B. subtilis and B. licheniformis. The second phase was the characterization of the two bacteria in terms of their tolerance to an acidic condition, temperature, and bile salt concentration. The measured parameter was the number of colonies in predetermined acidic conditions, temperatures, and bile salt concentrations. The number of growing bacterial colonies was calculated using the total plate count method. Results show that B. subtilis had an optimal growth point at the eighth hours, achieving a total population of 6.138x1013 CFU/mL, while the optimal growth point for B. licheniformis was reached at the tenth hour with 4.299x1013 CFU/mL. Bacillus subtilis and B. licheniformis were also tolerant at 40, 50, and 60Â°C. The acid tolerance testing was conducted at pH of 2, 4, and 6. It was revealed that Bacillus subtilis were intolerant to acidic condition at pH = 2, in which the number of colonies decreased drastically. On the contrary, B. licheniformis was tolerant to pH = 2, which was evident from the absence of a drastic decrease in the number of colonies. Both B. subtilis and B. licheniformis were tolerant to pH 4 and 6. High tolerance to 0.3% and 0.5% bile salt concentration was observed in both Bacillus subtilis and B. Licheniformis with a high number of colonies of 1010 CFU/mL. Therefore, it is concluded that both B. subtilis and B. licheniformis can be developed into probiotics.